IMPROVING MEMORY CHARACTERISTICS IN CHILDREN WITH DYSARTHRIC SPEECH DEFICIENCY - Iminjonova Mokhichehra Alimardon qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2026)
This article analyzes the specific features of memory process formation in children with dysarthric speech disorders, neuromotor and psychological factors influencing memory development, as well as effective methods for improving memory. The study covers exercises that develop verbal, visual, motor, and auditory memory, sensorimotor training, and speech therapy techniques. The article scientifically substantiates that memory development is an important factor in eliminating speech deficits associated with dysarthria. Finally, practical recommendations are provided for speech therapist-teachers.